The Implementation Of The Quantum Teaching Instructional Model In Improving Aqidah Akhlak Learning Outcomes For 8th-Grade Students At Mts Darussalam Pungging District, Mojokerto Regency - Tarisa Febrianti; Achmad Yusuf; Ahmad Ma’ruf (Educare: Journal Educational and Multimedia, 2023)
The character education model and national education goals encouraged researchers to develop a lesson that could improve the learning outcomes of Aqidah Akhlak in students. The learning conducted by the 8th-grade Islamic Religion Education Teachers was considered unsuccessful, as only 27 out of 40 students or 67,5% reached the KKM (Minimum Completion Criteria), and only 13 students or 32,5% achieved the KKM. This was evident due to the students' lack of active participation and enthusiasm, low response and interest, and difficulty in developing ideas during the learning process. To address these issues, an effective strategy was implemented to improve students' abilities using the Quantum Teaching learning model. This strategy aimed to create an active and enjoyable learning atmosphere, boost students' self-confidence, and increase their learning motivation and outcomes in Aqidah Akhlak lessons at MTs Darussalam in Pungging District, Mojokerto Regency. The study used a qualitative or critical approach through four stages of classroom action research: (1) action plan, (2) implementation of actions, (3) observation, and (4) reflection. The data for this research consists of the Quantum Teaching instructional model. Process data is obtained from student learning activities during the stage of giving motivation, structuring the learning environment, learning styles, and taking notes. Data results are obtained from student essays. The main instruments used in this study are the researcher, assisted by the collaborator teacher, using a guide sheet for observing student activities, and a rubric guideline for assessing essay results. The success criterion for learning Aqidah Akhlak in this study was set at 32,5% of students reaching the KKM, which is 76. However, based on the research findings, it was concluded that the target standardization of at least 92,5% of students achieving proficiency had not been met. Therefore, cycle I was necessary, followed by cycle II to improve learning outcomes until reaching the 92,5% proficiency level. With this achievement, it can be stated that the established learning model was acceptable, specifically the application of the Quantum Teaching learning model in enhancing learning outcomes for 8th-grade students at MTs Darussalam Pungging Mojokerto